2005
DOI: 10.1002/ijc.21285
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the MMP inhibitor MMI270 against lung metastasis following removal of orthotopically transplanted human colon cancer in rat

Abstract: We have investigated the antitumor effects of synthetic MMP inhibitor MMI270 against postoperative lung metastasis from colon cancer in nude rat. The KM12SM human colon cancer cells were injected into the cecal wall, and at 5 weeks after the injection, the cecum was removed including the tumor. Then, 30 mg/kg of MMI270 was administered perorally twice per day for 2 or 4 weeks, either immediately after removal or after week 2 after the removal. At week 7 after the removal, lung metastasis was significantly inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…The expression of MMP-9 was enhanced in a variety of malignant tumors, cultured tumor cells and oncogene transformed cells. In vitro migration assay confirmed that the high invasive ability of tumor is associated with the high expression of MMP-9 (19)(20)(21).…”
Section: Introductionsupporting
confidence: 53%
“…The expression of MMP-9 was enhanced in a variety of malignant tumors, cultured tumor cells and oncogene transformed cells. In vitro migration assay confirmed that the high invasive ability of tumor is associated with the high expression of MMP-9 (19)(20)(21).…”
Section: Introductionsupporting
confidence: 53%
“…Many novel MMP inhibitors effectively suppress neovascularization of tumors developing in experimental metastasis models. A synthetic MMP inhibitor (MMI270) administered early after postoperative primary tumor removal, demonstrated antitumor effects for lung metastases originating from colon cancer in nude rats [110]. Mechanistically, the findings confirmed that MMP inhibition diminishes neovascularization of metastases.…”
Section: Mmp Inhibition Targeting Angiogenesismentioning
confidence: 62%
“…This point is highlighted by the results of a study involving a synthetic MMPI, MMI270, in a rat model of colon cancer metastasis [46]. MMI270 competitively binds to zinc in the active state of several MMPs including MMP-1, -2, -3, -9 and -13 resulting in their inhibition.…”
Section: Targeting Mmps In Cancer Therapy and Future Directionsmentioning
confidence: 99%